Act1 out of Action: Identifying Reliable Reference Genes in Trichoderma reesei for Gene Expression Analysis - Caroline Danner; Yuriy Karpenko; Robert L. Mach; Astrid R. Mach-Aigner (Journal of Fungi)
Trichoderma reesei is a well-established industrial enzyme producer and has been the subject of extensive research for various applications. The basis of many research studies is the analysis of gene expression, specifically with RT-qPCR, which requires stable reference genes for normalization to yield reliable results. Yet the commonly used reference genes, act1 and sar1, were initially chosen based on reports from the literature rather than systematic validation, raising concerns about their stability. Thus, properly evaluated reference genes for T. reesei are lacking. In this study, five potentially new reference genes were identified by analyzing publicly available transcriptome datasets of the T. reesei strains QM6a and Rut-C30. Their expression stability was then evaluated under relevant cultivation conditions using RT-qPCR and analyzed with RefFinder. The two most stable candidate reference genes were further validated by normalizing the expression of the well-characterized gene cbh1 and comparing the results to those obtained using act1 and sar1. Additionally, act1 and sar1 were normalized against the new reference genes to assess the variability in their expression. All five new reference genes exhibited a more stable expression than act1 and sar1. Both in silico and RT-qPCR analysis ranked the so far uncharacterized gene, bzp1, as the most stable. Further, we found that act1 and sar1 have strain- and condition-dependent expression variability, suggesting that they are unsuitable as universal reference genes in T. reesei. Based on these results, we propose to use the combination of bzp1 and tpc1 for the normalization in RT-qPCR analysis instead of act1 and sar1.